Association of MUC2 and CYP11B2 genes single nucleotide polymorphisms with the external genital endometriosis development in female patients of the Slavic population of the Russian Northwestern Federal District - Natal'ia V. Kulikova; Inna I. Kovalenko; Larisa S. Litvinova; Natal'ia V. Shperling; Andrei V. Ivanov; Daria A. Skuratovskaia; Dmitrii V. Baibuz; Ianina A. Lebedeva; Evgeniia M. Pestun (IP Berlin A.V., 2020)
Aim. Search for the association of polymorphisms C(-15161)T (rs10902088) and T(-12150) C(rs10794288) of the MUC2 gene and С(-344)Т (rs1799998) of the CYP11B2 gene with the increased risk of genital endometriosis development in the Slavic population. Materials and methods. The study included 85 female patients (from 19 to 44 years old) with a diagnosis of genital endometriosis and 79 healthy women (from 20 to 42 years old). Genotyping was performed by real-time PCR using a Light Cycler 480 Instrument II amplifier (Roche, Switzerland). Polymorphism determination kits, MUC2 C(-15161)T (rs10902088), MUC2 T(-12150)C (rs10794288), CYP11B2 С(-344)Т (rs1799998) (CJSC Syntol). Results. It was found that the CC genotype of the T(-12150)C (rs10794288) C polymorphism of the MUC2 gene and the C(-344)T (rs1799998) CC polymorphism genotype of CYP11B2 gene are protective against endometriosis, and the TT genotype of C(-344)T polymorphism ( rs1799998) of the CYP11B2 gene contributes to the development of this disease. Conclusion. The search for molecular genetic aspects in the development of genital endometriosis is necessary for early diagnosis and prognosis of the disease.